Reliability assessment of the vertical well system subjected to erosion and tubing failure - Mustaffa, Z. (Taylor and Francis Ltd., 2021)
Tubing is part of a typical vertical well system which functions to transport hydrocarbon from the producing formations to the field surface facilities for processing. With its exposure to the harsh sandstone reservoir environment, erosion is likely to be present in the tubing. Regardless of this, the existing burst design models have not considered the impact from erosion when carrying out the assessment of the tubing. This paper proposes an erosion model to be integrated into the existing burst strength models and the assessments to be carried out using probabilistic approaches. Herein, limit state functions were introduced for the tubing and reliability assessment of the structure was computed by means of probability of failures (P f) under varying reservoir pressures (P op). Comparisons were made between the models computed with and without the inclusion of erosion models, for a well currently operated in the Peninsular Malaysia Operation. Â© 2020 Informa UK Limited, trading as Taylor & Francis Group.